SYNTAX Score II as a Predictor of One-Year Major Adverse Cardiovascular Events in Patients with Chronic Coronary Syndrome and Type 2 Diabetes Mellitus Undergoing Percutaneous Coronary Intervention - Elsa Tamara Saragih; Harris Hasan; Abdul Halim Raynaldo; Cut Aryfa Andra; Teuku Bob Haykal; Kamal Kharazzi Ilyas (Talenta Publisher, 2026)
Background: The severity of coronary atherosclerotic lesions is an important determinant of cardiovascular events in patients with CAD. The SS-II (SYNTAX-II) score, which integrates anatomical characteristics with clinical variables, provides improved prognostic value compared with anatomical scoring alone. Objective: To determine whether the SS-II predicts one-year MACE in CCS patients with T2DM who undergo PCI. Methods: This observational analytic study employed a retrospective cohort design including patients treated from June 2023 to August 2024. A total of 128 CCS patients with T2DM who underwent PCI were enrolled. Bivariate and multivariate analyses were performed to examine the association between the SS-II and MACE. One-year MACE-free survival was analyzed using Kaplan–Meier curves. Results: MACE occurred more frequently among patients with high SS-II scores (22 [34.4%], P < 0.001). Mortality and acute heart failure were both significantly associated with the SS-II (P = 0.042 and P = 0.03, respectively). Patients with high scores had significantly lower one-year MACE-free survival. Conclusion: The SS-II is a valuable predictor of one-year MACE in CCS patients with T2DM undergoing PCI.